Investing in the Future: Unveiling the Financing Architecture of Islamic Early Childhood Education at MGI Kindergarten, Handapherang, Ciamis - Aprila, Moch Dicky; Huda, Mila Imalatul (Bestari, 2025)
This study aims to analyze the financing system of early childhood education at MGI Handapherang Kindergarten in Ciamis. Employing a qualitative approach, data were collected through interviews, direct observations, and document analysis. The findings reveal that the financing system at the institution involves multiple stakeholders, including the government, parents, and the local community. Several factors influence the effectiveness of this system, such as the level of parental involvement, government policies, and the availability of resources. One of the central challenges identified is the limited financial support from both governmental and parental sources. The study underscores the vital role of collaborative efforts among stakeholders in ensuring equitable, high-quality, and sustainable early childhood education. Data were obtained through interviews with key informants—including school administrators, parents, and local government representatives—complemented by on-site observations of payment and administrative procedures, as well as a review of relevant documents, such as financial reports, policy guidelines, and records of parental participation in school activities.